2004
DOI: 10.1111/j.1460-9592.2004.01303.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low dose ketamine before induction on propofol anesthesia for pediatric magnetic resonance imaging

Abstract: Intravenous administration of low dose ketamine before induction and maintenance with propofol preserves hemodynamic stability without changing the duration and the quality of recovery compared with propofol alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
59
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 20 publications
(24 reference statements)
6
59
1
Order By: Relevance
“…Several investigators, in various studies which were done, found that the co administration of ketamine with propofol during induction prevented the adverse haemodynamic outcomes which were seen when propofol was used alone [5,6]. Several strategies, including IV administration of 0.5 mg/kg ketamine prior to propofol induction and infusion, have been shown to decrease adverse haemodynamic events which were associated with isolated use of propofol [5].…”
Section: Resultsmentioning
confidence: 99%
“…Several investigators, in various studies which were done, found that the co administration of ketamine with propofol during induction prevented the adverse haemodynamic outcomes which were seen when propofol was used alone [5,6]. Several strategies, including IV administration of 0.5 mg/kg ketamine prior to propofol induction and infusion, have been shown to decrease adverse haemodynamic events which were associated with isolated use of propofol [5].…”
Section: Resultsmentioning
confidence: 99%
“…administration of katamine. 14,15 In this study group A having highest fraction of ketamine in ketofol so the blood level of ketamine rises rapidly. LMA insertion time was significantly (p-0.0089) less in groups C and D comparing group A and B. Ketamine produces increase in muscle tone some time spasm.…”
Section: Discussionmentioning
confidence: 81%
“…10 Tomatir et al reported that, use of small dose of Ketamine 0.5 mg/kg allows successful scan completion with lower induction and maintenance doses of propofol beside haemodynamic stability. 11 Eirch et al in their observational study found single dose of ketamine 0.5 mg/kg reduced propofol requirement for paediatric MRI compared to propofol and propofol ketamine group with faster recovery after scan completion. 12 Study has shown combination of Propofol and Ketamine is a better sedation with less side effects than using either drug alone.…”
Section: Discussionmentioning
confidence: 97%